Preventive Effect of TU-100 on a Type-2 Model of Colitis in Mice: Possible Involvement of Enhancing Adrenomedullin in Intestinal Epithelial Cells - Atsushi Kaneko; Toru Kono; Naoko Miura; Naoko Tsuchiya; Masahiro Yamamoto (Gastroenterology Research and Practice)
Purpose. Crohn's disease (CD) and ulcerative colitis (UC), the two major forms of inflammatory bowel disease (IBD), have histopathologically and immunologically different characteristics. We previously reported that a traditional Japanese medicine, daikenchuto (TU-100), ameliorated a trinitrobenzenesulfonic acid- (TNBS-) induced type-1 model colitis exhibiting histopathological features of CD through adrenomedullin (ADM) enhancement. Our current aims were to examine whether TU-100 ameliorates a type-2 model colitis that histologically resembles UC and identify the active ingredients. Methods. TU-100 was administered orally to mice with oxazolone- (OXN-) induced type-2 model colitis. The morbidity was evaluated by body weight loss and the macroscopic score of colonic lesions. ADM was quantified using an EIA kit. Results. TU-100 prevented weight loss and colon ulceration. ADM production by intestinal epithelial cells was increased by TU-100 addition. Screening to identify active ingredients showed that [6]-shogaol and hydroxy α-sanshool enhanced ADM production. Conclusions. TU-100 exerted a protective effect in OXN-induced type-2 model colitis, indicating that TU-100 may be a beneficial agent for treatment of UC.